The influence of obesity on operating room time and perioperative complications in cochlear implantation - Jonathan L. Hatch (KeAi Communications Co., Ltd., 2017)
Objective: The rising incidence of obesity in the United States is associated with increased healthcare expenditures and resource allocation. Obesity has been associated with prolonged operating times during surgical procedures. The primary objective of this study is to compare body mass index (BMI) to length of surgery during cochlear implantation. Methods: A retrospective case control study from a tertiary academic referral center was performed. Patients included were adults who underwent primary, single-sided cochlear implantation with documented BMI and operating room (OR) times from January 2009 to July 2015. The following data were collected: BMI, total operating room time (TORT), surgical operating room time (SORT), ASA status, perioperative and postoperative complications, age, and gender. Results: Two hundreds and thirty-four patients were included and stratified into obese (BMI >30) and non-obese (BMI < 30) categories. Statistical analysis was performed comparing TORT against the obesity category along with other variables. Independent sample t-test demonstrated that obesity increases TORT and SORT by 16.8 min (P = 0.0002) and 9.3 min (P = 0.03), respectively, compared to the non-obese group. Multivariate linear regression analysis demonstrated no statistically significant impact of gender, or ASA status on total operating or surgical time. Obesity was associated with increased perioperative complications (odds ratio [OR], 6.21; 95% CI, 1.18–32.80; P = 0.03) and postoperative complications (OR, 3.97; 95% CI, 1.29–12.26; P = 0.02). Conclusions: Obesity leads to longer TORT and SORT during primary cochlear implant surgery. Obesity is also associated with increased perioperative and postoperative complications compared to non-obese patients. These data have implications with utilization of operating room resources. Keywords: Cochlear implant, Body mass index, Operating time, Perioperative complications